Ziphius cavirostris G. Cuvier 1823 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Ziphius cavirostris G. Cuvier, 1823. Rech. Oss. Foss., 5:350. TYPE LOCALITY: France, Bouches-du-Rhone, between Fos and the mouth of the Galegeon River. DISTRIBUTION: Worldwide, tropical, temperate, and subarctic waters. PROTECTED STATUS: CITES - Appendix II as Order Cetacea. ISIS NUMBER: 5301411005006001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Cetacea, pp. 290-304 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 302, DOI: 10.5281/zenodo.7352983